Biochemical Evaluation of Siddha Formulation Pitha Karappan Chooranam - Miraaj, R.; Shyamala, K.; Soundararajan, D.K. (World Journal of Pharmacy and Pharmaceutical Sciences, 2023)
Background: Pitha Karappan can correlated with the modern term of Atopic dermatitis treating by siddha herbal formulation Pitha Karappan Chooranam is mentioned in the book of Sarabenthirar Vaithiya Muraigal (Virana Karapan Roga Sikitchai) as internal medicine. Aim & Objective: The aim of this study is to evaluate the Biochemical analysis of Pitha Karappan Chooranam. Methodology: The Biochemical analysis of Pitha Karappan Chooranam is carried out using standard procedures on January 2023 at Central Council for Research in Siddha unit (CCRS), Govt/Siddha College and Hospital, Palayamkottai, Tirunelveli, India. Results: Preliminary Biochemical screening found, the presence of Sulphate, Chloride, Starch, Tannic acid, Ferrous ion, Unsaturated compound and Aminoacid. Discussion: Sulphate- are a type of cleansing agent known as an anionic surfactant. surfactants bind with dirt, oil, and other impurities on the hair or skin, making them easier to wash away, Chloride- will help to exfoliate the top layers of skin, removing excess oil, dirt, and other impurities that may have accumulated during the day, Starch- helps buff away dead skin cells by gently exfoliating the skin. Dead skin cells tend to clog pores, which can eventually result in acne breakouts and leave scars. Starch can help remove these dead skin cells, thus rejuvenating the skin, Tannic acid- Tannins have natural antimicrobial properties that help reduce acne breakouts and blemishes. Tannins contain anti-inflammatory properties that can help minimize redness and inflammation, reduce cell damage, tannins act as an antioxidant against free radicals, Ferrous ion- helps with optimizing the skin's wound healing function and minimizing the appearance of bruises. increasing iron will often make the itchiness go away, Unsaturated compound - control symptoms related to inflammation, Aminoacid- help restore cracked, flaky, or dry skin and maintain overall skin health. Conclusion: This study is an effort to explore the different Biochemical compounds of Pitha Karappan Chooranam effective in the management of Pitha Karappan (Atopic Dermatitis).
Keywords: Biochemical; Atopic dermatitis; Pitha Karappan Chooranam; Pitha Karappan